Experimental studies of a hybrid peeling process for cassava roots - Adegoke, A.; Oke, M.; Oriola, K.; Adekoyeni, O.; Sanni, L.; Adebowale, A.R. (2024)
Peeling is an essential unit operation prior to further processing of cassava. This study presents a experimental studies on functional and proximate parameters of gari and HQCF as affected by peeling methods and cassava cultivars. A newly developed abrasive peeling machine with the dual function of mechanical and mild chemical peeling of cassava roots by recycling of fruit water was used in the peeling process. Peeling of cassava by hands were used as control for this study. The peeling machine utilizes abrasive peeling surface inscribed with indented 0.12 cm stainless steel of 77cm height with 245cm diameter, a concrete based cavity, fruit water recovery tank, water pump and the transmission system. The fruit water was used to soak the cassava tubers before peeling with the machine for 60 minutes. Improved cassava varieties: TMS 30572 and TME 419 were used. High quality cassava flour (HQCF) and gari were produced from the varieties with three different peeling methods: manual, mechanical and mechanical/chemical (hybrid). Results obtained from the HQCF produced from tubers that were peeled manually, mechanically and hybrid peeling using TMS 30572 and TME 419 cassava varieties were: moisture content (10.90–11.36% db), crude protein (0.24–0.35%), carbohydrate content (88.24–88.86%) and ash content (0.09–0.30%) while results of values for bulk density, swelling capacity, WAC, solubility, LGC and pH were (0.55–0.68 g/ml),(854.38–862.38%),(122.5–152.5%),(6.00-6.80%),(5.00–6.67%) and (5.50–6.92) respectively. Cyanide content (1.98-4.04 mg/kg) and OAC (128-144%). The gari’s proximate and functional compositions values were: moisture content (6.00–6.86% db), crude protein (1.32–1.59%), crude fat (0.30–0.52%), crude fibre (2.21–2.58%), CHO (88.02–90.50%) and ash content (0.71–0.82%). The bulk density (0.560–0.675 g/ml), swelling power (827–. 38%), WAC (318.21–435.39%), cyanide content (1.92-3.14 mg/kg) and pH (4.35–5.00). HQCF and gari had proximate and functional properties that compared favorably with those of manual peeling of cassava for the products. The functional properties were well improved by the hybrid and mechanical peeling methods.